The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/molecules28217269
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Foods of Plant Origin as Sources of Vitamins with Proven Activity in Oxidative Stress Prevention according to EFSA Scientific Evidence

María Ciudad-Mulero,
Laura Domínguez,
Patricia Morales
et al.

Abstract: Beyond their nutritional benefits, vitamins could decrease the risk of chronic diseases due to their potent antioxidant capacity. The present work is aimed at reviewing the state of the art regarding (1) the vitamins involved in oxidative stress prevention in accordance with the requirements established by the European Food Safety Authority (EFSA) and (2) the foods of plant origin that are sources of those vitamins and have potential benefits against oxidative stress in humans. According to the European regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…When discussing fat-soluble vitamins, we should also mention vitamins A and E, with the latter comprising tocopherols and tocotrienols. Dietary sources of vitamin E include nuts, almonds, plant oils (especially olive oil), and sprouts [ 59 ]. Although there is no available research indicating the anti-cancer effects of vitamin E on HCC development or progression, its anti-inflammatory properties are utilized in the treatment of liver steatosis and inflammation.…”
Section: Vitamins and Trace Elements As Supportive Elements In The Pr...mentioning
confidence: 99%
“…When discussing fat-soluble vitamins, we should also mention vitamins A and E, with the latter comprising tocopherols and tocotrienols. Dietary sources of vitamin E include nuts, almonds, plant oils (especially olive oil), and sprouts [ 59 ]. Although there is no available research indicating the anti-cancer effects of vitamin E on HCC development or progression, its anti-inflammatory properties are utilized in the treatment of liver steatosis and inflammation.…”
Section: Vitamins and Trace Elements As Supportive Elements In The Pr...mentioning
confidence: 99%
“…The growth and resilience of chickens to oxidative stress are influenced by the antioxidant properties of riboflavin and its role in protein synthesis. Numerous investigations have shown that riboflavin is required for optimum hatchability ( Ciudad-Mulero et al, 2023 ; Mahmudiono and Haliman, 2023 ). The coenzymes flavin adenine dinucleotide and flavin mononucleotide, which are required for numerous redox actions in significant metabolic processes like the mechanism of the antioxidant system and the production of energy, require riboflavin ( Lienhart et al, 2013 ; Kanwal et al, 2024 ).…”
Section: Introductionmentioning
confidence: 99%
“…Riboflavin plays an essential part in the antioxidant system. Its involvement in aerobic cell oxidation processes is particularly significant ( Ciudad-Mulero et al, 2023 ). Glutathione disulfide is converted to reduced glutathione ( GSH ) by the enzyme glutathione reductase, which relies on flavin adenine dinucleotides.…”
Section: Introductionmentioning
confidence: 99%